Airport capacity constraints and air traffic demand in China. (August 2022) - Hu, Rong; Feng, Huilin; Witlox, Frank; Zhang, Junfeng; Connor, Kevin O.
Abstract: This paper analyzes the degree of airport capacity utilization of 239 China's civil airports in 2019. Our database is unique and very detailed in that we combine actual operation and scheduled flight data. We are particularly interested in the list of capacity constrained airports, their characteristics, and future development. To this end, we develop a classification matrix to investigate capacity constrained airports. We then forecast the demand and capacity of these airports under three scenarios and use the data as inputs for Monte Carlo simulation, to predict the capacity utilization trends of these airports in 2025 and 2035. Our research shows that: (1) There are significant differences between airports in terms of airport congestion status, and over 85% of airports in China experience no overload; (2) Big spatial differences are observed in the distribution of airports with less spare capacity and can be summarized as "more in eastern China and less in western China"; (3) Ten airports stand out as seriously capacity constrained and all of them serves as international or regional hubs; (4) Airport location, airport orientation, and linkage to the local economy are closely related to airport capacity constraints; (5) As most constrained airports are going to increase capacity in the future, as well as the outbreak of COVID-19 negatively affected aviation demand, most airports will have sufficient capacity reserves in the future. However, Shenzhen Bao'an and Xi'an Xianyang International Airport will face heavy capacity pressure. We also provide several recommendations to improve airport capacity utilization and relieve capacity shortages. Highlights: a new classification method is developed to identify capacity-constrained airport. Big spatial differences are observed in terms of airport spare capacity. Airport location and positioning, politics and economics significance are closely related to capacity utilization. Only Shenzhen Bao'an and Xi'an Xianyang Airport will face heavy capacity pressure in the future.